From Potential to Performance: Training Practice and Performance Preparation in Conservatoires - Altenmüller, Eckart; Arjas, Päivi; Van den Bergen, Marijke; Borgdorff, Henk (The Hague Royal Conservatoire, 2014)
This conference addresses the question "What is needed to prepare performing musicians in the 21st century?" It is designed to give space for the interaction of teachers at the Royal Conservatoire in workshops, clinics and lectures with relevant and up-to-date information from many fields and disciplines related to teaching performing musicians. The aim is also to provide students with material to help them with self-training. Many themes connected to teaching and learning practicing and performing skills, as well as injury prevention, will be presented by recognised experts, all of whom are also accomplished musicians (see resumes below). The conference will include lectures as well as more interactive forms such as workshops, and also special clinics designed for a particular instrument group or on a particular theme. Participants can sign up for the workshops and clinics of their choice on Saturday. More information and a detailed programme on the content will be available in the coming week. All lectures and formal discussions will be in English. Teachers from the KC can receive an allowance in extra hours as mentioned in the information letter from Martin Prchal. Fridays theme is 'Overview of Existing Programmes'' where the guests will each present a talk on the program for teaching or assisting performing musicians at their institution.Saturday title is 'Practicing and Performing Skills and will offer lectures, workshops and clinics to explore many aspects of motor learning and motivation.On Sunday, 'Perspectives for the Future' will offer a workshop on 'Deliberate Practice' and a discussion about what is needed as well as the obstacles for institutions and teachers to teach performing musicians in the 21st century.Susan Williams, Wieke Karsten and Henk Borgdorff will be moderating the sessions, and Marijke van den Bergen is in charge of organization.
Keywords: Music education